Development and Pilot Implementation of a Nutrition Curriculum and Rotation in Pediatric Gastroenterology Fellowships. Issue 2 (February 2019) - Shaikhkhalil, Ala; Jump, Candi; Goday, Praveen S.
Abstract : ABSTRACT: Structured nutrition rotations are rarely offered in pediatric gastroenterology fellowships. The North American Society for Pediatric Gastroenterology, Hepatology, and Nutrition (NASPGHAN) Nutrition Committee developed a curriculum to serve as the basis for a rotation in clinical nutrition. We worked directly with 5 fellowship programs to tailor the experience to individual institutions. As part of our pilot study, fellows completed knowledge assessments and self-assessment of comfort level at the start and end of the experience. We saw a trend in improvement of comfort level and increase in mean score on knowledge assessments, but the differences did not meet statistical significance. Fellows who completed the rotation had an increase in comfort level in all topics with most dramatic increases in nutrition management of cystic fibrosis, refeeding syndrome, and cholestasis. Objective measures of nutrition knowledge attainment and use of programmatic feedback to continually improve the learners' experience will help expand the nutrition curriculum to a broader audience. Abstract : Supplemental Digital Content is available in the text